Verso l’abolizione dell’identità di genere ne Il corpo odiato di Nicola Lecca - Kłosek, Wiesława (Romanica Silesiana)
Towards the Abolition of Gender Identity in Il corpo odiato by Nicola Lecca Gabriele, the main character of the novel by Nicola Lecca, discovers within himself a homosexual inclination which doesn’t conform to a traditional masculinity. Thus, it causes identity crisis. The protagonist carries out an obsessive auto analysis. He tries to represent self-discipline. This should lead him to regain confidence and social assimilation. The Article shows three stages, which Gabriele goes through: the ideal type of masculinity, the protest period and the discovery of his real identity. All three describe a subordination, an attempt to get the autonomy back and the awareness of freedom. This process was analysed in a range of few components: the main character’s space, his social relations, his homosexual experience, judging his own body, the emotional conflict between trying to be perfect, low self-esteem and the act of writing. Nicola Lecca’s text may be read as a voice in discussion about stereotypical masculine pattern which in this case is questioned. Key words: gender identity, stereotypical masculine pattern, homosexuality, Italian modern literature.